Optimization of Alumina Slurry for Oxide-Oxide Ceramic Composites Manufactured by Injection Molding - Catherine Billotte; Edith Roland Fotsing; Edu Ruiz (Advances in Materials Science and Engineering)
This paper focuses on the rheological study of an alumina suspension intended for the manufacturing of oxide-oxide composites by flexible injection. Given the production constraints, it is required to have stable suspension with low viscosity and a Newtonian behavior. This is achieved with a concentration of nitric acid between 0.08 wt% and 0.2 wt% and amount of 3 wt% of PVA binder. The maximum loading of the suspension of 47 vol% suggests that there is no structure development within the suspension with optimized concentration of acid and PVA.